Micrococcal Nuclease stimulates Staphylococcus aureus Biofilm Formation in a Murine Implant Infection Model - Forson, Abigail M.; Rosman, Colin W. K.; van Kooten, Theo G.; van der Mei, Henny C.; Sjollema, Jelmer (Frontiers in Cellular and Infection Microbiology, 2022)
Advancements in contemporary medicine have led to an increasing life expectancy which has broadened the application of biomaterial implants. As each implant procedure has an innate risk of infection, the number of biomaterial-associated infections keeps rising. Staphylococcus aureus causes 34% of such infections and is known as a potent biofilm producer. By secreting micrococcal nuclease S. aureus is able to escape neutrophil extracellular traps by cleaving their DNA-backbone. Also, micrococcal nuclease potentially limits biofilm growth and adhesion by cleaving extracellular DNA, an important constituent of biofilms. This study aimed to evaluate the impact of micrococcal nuclease on infection persistence and biofilm formation in a murine biomaterial-associated infection-model with polyvinylidene-fluoride mesh implants inoculated with bioluminescent S. aureus or its isogenic micrococcal nuclease deficient mutant. Supported by results based on in-vivo bioluminescence imaging, ex-vivo colony forming unit counts, and histological analysis it was found that production of micrococcal nuclease enables S. aureus bacteria to evade the immune response around an implant resulting in a persistent infection. As a novel finding, histological analysis provided clear indications that the production of micrococcal nuclease stimulates S. aureus to form biofilms, the presence of which extended neutrophil extracellular trap formation up to 13 days after mesh implantation. Since micrococcal nuclease production appeared vital for the persistence of S. aureus biomaterial-associated infection, targeting its production could be a novel strategy in preventing biomaterial-associated infection.